2002
DOI: 10.1289/ehp.02110991
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from lung cancer in workers exposed to sulfur dioxide in the pulp and paper industry.

Abstract: Our objective in this study was to evaluate the mortality of workers exposed to sulfur dioxide in the pulp and paper industry. The cohort included 57,613 workers employed for at least 1 year in the pulp and paper industry in 12 countries. We assessed exposure to SO(2) at the level of mill and department, using industrial hygiene measurement data and information from company questionnaires; 40,704 workers were classified as exposed to SO(2). We conducted a standardized mortality ratio (SMR) analysis based on ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 39 publications
3
44
0
1
Order By: Relevance
“…In a former case-referent study on rheumatoid arthritis, pulp and paper workers were shown to have an increased risk (8). The authors related their finding to occupational exposure to respirable organic dust.…”
Section: Andersson Et Almentioning
confidence: 98%
See 3 more Smart Citations
“…In a former case-referent study on rheumatoid arthritis, pulp and paper workers were shown to have an increased risk (8). The authors related their finding to occupational exposure to respirable organic dust.…”
Section: Andersson Et Almentioning
confidence: 98%
“…There seems to be a short-term effect of sulfur dioxide air pollution levels with respect to ischemic heart diseases (28). In the IARC cohort of pulp and paper mill workers, mortality was reported for the workers exposed to sulfur dioxide (8). Among the workers never exposed, the mortality from diseases of the circulatory system reached an SMR value of 0.92 (95% CI 0.87-0.96), and for highly exposed workers the SMR was 0.96 (95% CI 0.86-1.07).…”
Section: Andersson Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have observed association of increased lung cancer risk with occupational and environmental exposure to SO 2 (Lee et al, 2002;Tseng et al, 2012). DNA methylation has emerged as a promising biomarker for environmental-related diseases, including lung cancer.…”
Section: Discussionmentioning
confidence: 96%